Inappropriate prescribing among ambulatory elderly patients in a geriatric centre in Southwestern Nigeria (2019)
0.05. Results: Mean age of patients was 69 ± 0.4 years (range 60-85 years) and 219 (65.4%) were females. An average of 4.2 medications per patient prescription was found. The Beers criteria identified 26.5% PIMs, while STOPP criteria identified 57.1% PIMs. START detected 29 PPOs in 15 (4.4%) of the patient’s prescription. The most prevalent disease conditions were hypertension 235 (70.1%) and osteoarthritis 64 (19.3%). Polypharmacy was significantly associated with PIMs use in both Beers (p=0.002) and STOPP (p=0.001) criteria. Conclusions: The prevalence of PIP is high among the elderly patients. The STOPP/START criteria identified a higher proportion of PIMs among elderly patients compared with Beers criteria. The frequency of PIP should stimulate efforts to curtail potentially inappropriate prescribing and may require the need for advocating for a national criteria to be adopted by health care professionals in Nigeria.